2021
DOI: 10.1186/s12876-020-01596-2
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in MicroRNA gene expression profile in liver transplant patients with hepatocellular carcinoma

Abstract: Background Hepatocellular carcinoma (HCC) can lead to liver failure which renders to liver transplant. miRNAs might be detected as biomarkers in subclinical stage of several hepatobiliary disorders like HCC. Therefore, in the present study, alterations in miRNAs as biomarkers were detected in LT patients with HCC. Methods Fourteen tissue samples composed of 5 rejected and 9 non-rejected ones were used for studying the miRNAs expression pattern usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Therefore, this miRNA might be used as a therapeutic target. A significant correlation between hsa-mir-4449 and the development of hepatocellular carcinoma and gastric cancer has been reported, 37 , 38 whereas miR-142 has tumor-suppressing properties against hepatocellular, colon, lung, and breast carcinoma. 39 Downregulation of hsa-mir-877 in an osteosarcoma cell line and tissues has been observed.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this miRNA might be used as a therapeutic target. A significant correlation between hsa-mir-4449 and the development of hepatocellular carcinoma and gastric cancer has been reported, 37 , 38 whereas miR-142 has tumor-suppressing properties against hepatocellular, colon, lung, and breast carcinoma. 39 Downregulation of hsa-mir-877 in an osteosarcoma cell line and tissues has been observed.…”
Section: Discussionmentioning
confidence: 99%
“…They found that miR-194-5p and miR-548as-3p are significantly upregulated, whereas miR-3158-5p and miR-4449 are significantly downregulated in patients experiencing rejection when compared with stable adults. 73 Conversely, Zhang et al 8 revealed that miR-18b-340 and miR-106b were upregulated in peripheral blood mononuclear cells of long-term, stable LT recipients relative to both healthy adults without LT and recipients experiencing rejection. Early successes with miRNAs may stem from their roles in allograft injury pathways, including causative and signaling functions.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of molecular biology, miRNA in regulating cancer pathogenesis has been a major achievement over the past decade [ 9 ]. This type of RNA comprises nearly 5% of transcriptome and regulates approximately 25% of genes in humans [ 10 ]. The miRNA can inversely modulate gene expression via directly inducing messenger RNA degradation by base pairing with complementary sites in the 3′-untranslated regions.…”
Section: Introductionmentioning
confidence: 99%